Evaluasi, Penilaian, Tes, dan Pengukuran dalam Pembelajaran: Analisis Konseptual dan Implikasinya terhadap Praktik Pendidikan - Rismayana Johan; Saridah; Maulina M (Malewa: Journal of Multidisciplinary Educational Research, 2026)
Evaluation in learning is a crucial part of the educational process because it serves to determine the level of student success and the effectiveness of the learning process that has been implemented. In the world of education, the term "evaluation" is often equated with "assessment," "test," and "measurement," even though these four terms have different meanings and functions. This article aims to explain the meaning of evaluation, assessment, testing, and measurement, explain the similarities between these four concepts, and outline their differences in the context of learning. The method used in writing this article is a literature study by reviewing various sources of books and educational journals. The results of the discussion indicate that evaluation has the broadest scope because it encompasses the decision-making process regarding learning outcomes, while assessment focuses more on the process of assigning values ​​to students' abilities. Tests are used as a tool to obtain data, while measurement is the process of assigning numbers to learning outcomes based on certain rules. By understanding the relationship and differences between these four terms, educators can implement the learning process more effectively and objectively.